2003
DOI: 10.1088/1126-6708/2003/05/010
|View full text |Cite
|
Sign up to set email alerts
|

Universality classes for horizon instabilities

Abstract: Abstract:We introduce a notion of universality classes for the Gregory-Laflamme instability and determine, in the supergravity approximation, the stability of a variety of solutions, including the non-extremal D3-brane, M2-brane, and M5-brane. These three non-dilatonic branes cross over from instability to stability at a certain non-extremal mass. Numerical analysis suggests that the wavelength of the shortest unstable mode diverges as one approaches the cross-over point from above, with a simple critical expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
(95 reference statements)
3
25
0
Order By: Relevance
“…This result should be contrasted with the analysis of p-brane solutions in [8,9,10]. In those studies, it was found that for the ten-dimensional supergravity p-brane solutions with p ≤ 4, there is a threshold unstable mode for the neutral case, but this mode goes off to infinite wavelength at a critical value of the charge, signalling the disappearance of the instability.…”
Section: Uniform String Branchmentioning
confidence: 91%
See 3 more Smart Citations
“…This result should be contrasted with the analysis of p-brane solutions in [8,9,10]. In those studies, it was found that for the ten-dimensional supergravity p-brane solutions with p ≤ 4, there is a threshold unstable mode for the neutral case, but this mode goes off to infinite wavelength at a critical value of the charge, signalling the disappearance of the instability.…”
Section: Uniform String Branchmentioning
confidence: 91%
“…This is a natural extension of the investigation of p-branes in [6,8,9,10]. The two classes of solutions are related by T-duality, which implies that the thermodynamics of the smeared branes is identical to that of the p-brane with the same total number of extended directions.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A reason to be particularly interested in the GL instability for the near -extremal D2-D0 bound state is that it interpolates between near -extremal D2-branes, for which it is known there is no instability [5] and near-extremal smeared D0-branes, for which it has been argued that there is a GL instability [6,7,8]. The interpolation itself is interesting: the dynamics of the bound state has been argued to correspond to non-commutative field theory (NCFT) [9].…”
Section: Jhep02(2005)040mentioning
confidence: 99%